An Evolutionary Perspective on Why Food Overconsumption Impairs Cognition - Mattson, Mark P. (Trends Cogn Sci, 2019)
Brain structures and neuronal networks that mediate spatial navigation, decision-making, sociality and creativity evolved, in part, to enable success in food acquisition. Here I discuss evidence suggesting that the reason that overconsumption of energy-rich foods negatively impacts cognition is that signaling pathways that evolved to respond adaptively to food scarcity are relatively disengaged in the setting of continuous food availability. Obesity impairs cognition and increases the risk for some psychiatric disorders and dementias. Moreover, maternal and paternal obesity predispose offspring to poor cognitive outcomes by epigenetic molecular mechanisms. Neural signaling pathways that evolved to bolster cognition in settings of food insecurity can be stimulated by intermittent fasting and exercise to support the cognitive health of current and future generations.